Preliminary assessment of selected physico-chemical properties of peat water in relation to land use conversion in Leyte Sab-a Basin Peatland, Philippines - Shella S. Salamia; Syrus Cesar P. Decena; Michael S. Arguelles; Arwin O. Arribado; Lydia L. Robel (Annals of Tropical Research)
Tropical peatlands are unique wetland ecosystems that provide various ecosystem services such as carbon and water storage. However, these ecosystems have been significantly altered by anthropogenic activities. In this study, the impact of land use conversion on the selected physico-chemical properties of surface water in the Leyte Sab-a Basin Peatland was investigated. Surface peat water was collected from peat swamp forest, peatland converted to grassland and peatland under cultivation. The surface peat water temperature was measured on-site and the collected water samples were analyzed for turbidity, pH, dissolved oxygen (DO), nitrate (NO3-N), phosphate (PO4), and total dissolved solids (TDS). It was found that the physico-chemical properties of water such as temperature, pH, and TDS were significantly higher in disturbed land use (cultivation) areas. The direct relationship between the temperature of surface peat water to both phosphate and TDS suggests that increasing temperature brought by peatland conversion may directly lead to increasing phosphate and total dissolved solids concentration in water. Strong relationships were also found between TDS and phosphates as well as between pH and dissolved oxygen. Finally, the increasing trend of values of the examined peat water physico-chemical properties with land use disturbance (cultivation) indicates peatland degradation.